Fecal Calprotectin Responses Following Induction Therapy With Vedolizumab in Moderate to Severe Ulcerative Colitis: A Post Hoc Analysis of GEMINI 1. Issue 4 (5th October 2018) - Reinisch, Walter; Bressler, Brian; Curtis, Rebecca; Parikh, Asit; Yang, Huyuan; Rosario, Maria; Røseth, Arne; Danese, Silvio; Feagan, Brian; Sands, Bruce E; Ginsburg, Philip; Dassopoulos, Themistocles; et al.
Abstract: Background: In patients with ulcerative colitis (UC), fecal calprotectin (FC) concentrations correlate with endoscopic inflammation evidence. This study investigated the effect of vedolizumab induction on FC concentrations and whether FC concentrations could be a reliable surrogate measure of disease status. Methods: Data from the placebo-controlled, phase 3 trial GEMINI 1 were used to evaluate week-6 relationships between outcomes (including clinical remission, mucosal healing [MH], and endoscopic remission) and both absolute FC concentration values and relative FC concentration changes from baseline (%FC0-6 ). Sensitivity and specificity were calculated by cross-tabulation; the value of week-6 FC concentration as surrogate biomarker was measured with Youden J statistic computed for various cut points. Results: GEMINI 1 induction phase enrolled 895 patients. Fecal calprotectin concentration decreases were deeper in patients with clinical remission, MH, and/or endoscopic remission than in patients without. The best week-6 indicator of clinical or endoscopic remission in this data set was absolute FC concentration ≤150 µg/g. The surrogate biomarker values (based on areas under the curve) for the best-performing cut points (FC0-6 reduction >90%, FC ≤150 µg/g) were fair (range, 0.70–0.77, total population). More patients met the ≤150 µg/g cut point with vedolizumab than with placebo. Baseline FC concentrations were not correlated with clinical outcomes. Conclusions: Fecal calprotectin concentration reductions were greater with vedolizumab induction than with placebo. Week-6 FC concentrations had only fair surrogate biomarker value for endoscopic status. Our data suggest that, while FC may reflect inflammatory burden, FC concentration after vedolizumab induction may not be a robust biomarker of mucosal inflammation.